Who Might Be Interested in a Deep Borehole Disposal Facility for Their Radioactive Waste? - Neil A. Chapman (Energies, 2019)
The deep borehole disposal (DBD) concept for certain types of radioactive wastes has been discussed for many decades, but has enjoyed limited R&D interest compared to ‘conventional’ geological disposal in an excavated repository at a few hundreds of metres depth. This article explores the circumstances under which a national waste management programme might wish to consider DBD. Starting with an assumption that further R&D will answer technical issues of DBD feasibility, it examines the types of waste that might be routed to borehole disposal and the strategic drivers that might make DBD attractive. The article concludes by identifying the types of national programme that might wish to pursue DBD further and the pre-requisites for them to give it serious consideration.